Soil Organic Carbon Turnover Following Afforestation of a Savanna Revealed by Particle-Size Fractionation and Natural 13C Measurements in Ivory Coast - Thierry Desjardins; Thierry Henry Des Tureaux; Magloire Mandeng-Yogo; Fethiye Cetin (Land)
Soil organic matter plays a crucial role in the global carbon cycle, yet the magnitude and direction of changes in soil carbon content following vegetation shifts in the tropics remain highly debated. Most studies have focused on short-term changes, typically spanning only a few months or years. In this study, we investigated the medium-term dynamics of organic matter at a site where savanna, protected from fire for 58 years, has gradually transitioned to woodland vegetation. Natural 13C abundance analysis combined with particle-size fractionation was used to characterize the changes in SOM over time. While carbon content remains relatively stable, δ13C exhibits a distinct shift, particularly in the surface layers, reflecting the gradual replacement of savanna-derived carbon with tree-derived carbon. All fractions were influenced by the inputs and outputs of carbon from both savanna and tree sources. In the coarse fractions, most of the carbon originates from trees; however, a significant proportion of savanna-derived carbon (ranging from 10% to 40%, depending on the fraction, depth, and patch) persists, likely in the form of black carbon. In the fine fractions, nearly half of the carbon (40% to 50%) remains derived from the savanna, highlighting the greater stability of organic matter that is physically bound to clays and protected within microaggregates.